Ideia e projeto, construção e objeto: efeitos da fragmentação projeto-construção na prática arquitetônica - Carolina Pereira Rosa de Souza (2021)
The disparity between academic activity in the field of Architecture and the concrete reality of cities correlates with the distance between design practice and the reality of the material production of architectural objects, which instigates a critique of professional practice. Our research investigates, through a theoretical-critical approach, the spatial, temporal and epistemological fragmentation established between design and construction in the production of architecture and its effects on architectural practice. While design elaboration takes the form of a dialectical movement between idea and form, manifested in abstract representations; the relationship between such representations and the manipulation of matter is mostly a unidirectional movement, which implies conflicts both in production and in the final product. From the analysis of data collected at the Brazilian Council of Architecture and Urbanism and a questionnaire applied to architects who work in the area of design and construction, a discussion is fostered on the relations between idea, design, technique and material production with the aim of to rethink the architectural practice in face of the real production conditions.